Milk Street simple - Kimball, Christopher; Hirsch, J. M.; Locke, Michelle; Yanagihara, Dawn (Voracious/Little, Brown and Company, 2023)
"The James Beard Award-winning team at Milk Street delivers 200 easy, clever recipes you can just cook: the world's greatest culinary ideas, distilled to their essence and simplified for weeknight meals. Each of these 200 recipes works with just a handful of ingredients and short active cooking time; these dishes are done when you need them, or hands-off so you can let them cook while you do something else. The keys are high-impact ingredients, transformative techniques, powerful flavor combinations, and layers of texture. Milk Street Simple recipes help turn a straightforward bowl of pasta or a head of roasted cauliflower into a delightful meal, with no fuss and recipes that are endlessly flexible"--